Analisis Manajemen Supply Chain dalam Pengembangan Produk Export untuk Kerajinan Tangan Rotan di Cirebon - Elsa Silvia Nur Aulia (Jurnal Sosioteknologi, 2022)
This research is motivated by the fact that in Cirebon West Java, which is the largestrattan craftsman area in Indonesia, was found that there are many unresolved obstaclesin the development of rattan craft products that will be exported to several countries.The obstacles include the supply chain or the availability of raw materials, the lackof capital for small and medium industry (IKM) stakeholders, and the lack of humanresources management (HRM) as a form of regeneration for rattan craft craftsmen.This study used a qualitative approach where data were collected through observation,documentation, and interviews. The results of this study show that the problems facedby rattan handicraft producers are: 1) a lack of availability of raw materials caused bylong shipping distances, such as from Sulawesi and Kalimantan to Cirebon; 2) a lackof capital that can be absorbed by small entrepreneurs to continue to be able to run thisrattan craft business because of the lack of attention given to small entrepreneurs fromboth the government of Cirebon and the World Bank. 3) the lack of human resourcemanagement for rattan handicraft producers due to the lack of interest from the youngergeneration and the lack of a training platform for the younger generation to continuethis rattan craft relay from time to time.